2021
DOI: 10.3390/ijms222312941
|View full text |Cite
|
Sign up to set email alerts
|

Certain, but Not All, Tetraether Lipids from the Thermoacidophilic Archaeon Sulfolobus acidocaldarius Can Form Black Lipid Membranes with Remarkable Stability and Exhibiting Mthk Channel Activity with Unusually High Ca2+ Sensitivity

Abstract: Bipolar tetraether lipids (BTL) have been long thought to play a critical role in allowing thermoacidophiles to thrive under extreme conditions. In the present study, we demonstrated that not all BTLs from the thermoacidophilic archaeon Sulfolobus acidocaldarius exhibit the same membrane behaviors. We found that free-standing planar membranes (i.e., black lipid membranes, BLM) made of the polar lipid fraction E (PLFE) isolated from S. acidocaldarius formed over a pinhole on a cellulose acetate partition in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…Bipolar tetraether liposomes created from the polar lipid fraction of thermoacidophile archaeon Sulfolobus acidocaldarius have been studied by FTIR spectroscopy and SAXS [ 122 ]. Tetraether lipids were also shown to form stable black lipid membranes [ 128 ]. Although the whole phase diagram was not determined, a pressure-induced phase transition was detected from the shift of the symmetric CH 2 stretching mode.…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
“…Bipolar tetraether liposomes created from the polar lipid fraction of thermoacidophile archaeon Sulfolobus acidocaldarius have been studied by FTIR spectroscopy and SAXS [ 122 ]. Tetraether lipids were also shown to form stable black lipid membranes [ 128 ]. Although the whole phase diagram was not determined, a pressure-induced phase transition was detected from the shift of the symmetric CH 2 stretching mode.…”
Section: Pressure Effect On Some Biomoleculesmentioning
confidence: 99%
“…However, instability of the BLM made of conventional diester lipids has been a serious drawback [ 111 ]. Archaea tetraether lipids have been used to make BLMs (reviewed in [ 112 , 113 ]). Earlier studies [ 114 , 115 , 116 ] used archaea lipid extract to make free-standing planar membranes over micro-pores in a Teflon partition; however, those membranes lasted only 5–6 h or less, which was not superior to BLM made from diester lipids.…”
Section: Archaeal Planar Membranesmentioning
confidence: 99%
“…In contrast, in a recent study, PLFE has been shown to form stable BLM on the micro-pores of polydimethylsiloxane (PDMS) thin films embedded in a printed circuit board-based fluidics or in a glass/silicon microchip, exhibiting a constant electrical impedance for at least 55 h at 11–39 °C [ 117 , 118 ]. In a more recent study, it was demonstrated that BLM PLFE formed over a pinhole on a cellulose acetate partition in a dual-chamber Teflon device exhibited even more remarkable stability, showing a constant capacitance (~28 pF) for at least 11 days [ 113 ]. The extended stability may be related to the substrate material.…”
Section: Archaeal Planar Membranesmentioning
confidence: 99%
See 2 more Smart Citations